Epidemiology of Meropenem/Vaborbactam Resistance in KPC-Producing Klebsiella pneumoniae Causing Bloodstream Infections in Northern Italy, 2018 - Paolo Gaibani; Donatella Lombardo; Linda Bussini; Federica Bovo; Beatrice Munari; Maddalena Giannella; Michele Bartoletti; Pierluigi Viale; Tiziana Lazzarotto; Simone Ambretti (MDPI AG, 2021)
Meropenem/Vaborbactam (MEM-VAB) is a novel carbapenem- β-lactamase inhibitor active against KPC-producing Enterobacteria. Herein, we evaluate the incidence of meropenem/vaborbactam-resistance among KPC-producing K. pneumoniae (KPC-Kp) bloodstream infection in a large Italian hospital. Meropenem/vaborbactam-resistance was found in 8% (n = 5) KPC-Kp, while 5% (n = 3) strains exhibited cross-resistance to ceftazidime/avibactam (CAZ-AVI). Genomic analysis revealed that meropenem/vaborbactam-resistance was associated with truncated OmpK35 and insertion of glycine and aspartic acid within OmpK36 at position 134-135 (GD134-135). Notably, no specific mutation was associated to cross-resistance. No specific antimicrobial treatment was related to favorable clinical outcomes, while cross-resistance was not associated to higher clinical and/or microbiological failures. Our study indicated that resistance to meropenem/vaborbactam was due to porins mutations and is associated with reduced susceptibility to both ceftazidime/avibactam and carbapenems.